Prevention and management of hospital-acquired pressure injury among patients with lung disease in a hospital: a best practice implementation project. Issue 4 (14th December 2022) - Su, Jui-Yuan; Mu, Pei-Fan; Wang, Ching-Hui; Chen, Yu-Shang; Cheng, Ting-Yin; Lee, Mei-Yin
ABSTRACT: Objectives: The aim of this project was to promote evidence-based practice in the prevention and management of pressure injury in lung disease patients. Introduction: Pressure injury is a crucial quality indicator for hospital care of patients. The pressure injury incidence threshold in the chest wards has been exceeding that of the general ward (0.128%), which may extend patients' hospital stay. Methods: Clinical audits were performed using the JBI Practical Application of Clinical Evidence System and Getting Research into Practice (GRiP) audit and feedback tool. Twelve audit criteria representing best practice recommendations for preventing and managing pressure injury among lung disease patients were used. A baseline audit was performed to measure the degree of consistency between existing practice and best practice. This project used the GRiP analysis and multiple strategies to develop care protocols for pressure injury prevention and management. A follow-up audit was conducted to measure changes in clinical practice and pressure injury incidence. Results: Postimplementation audit compliance rates improved for the following criteria: skin assessment for identifying pressure injury indications (from 31 to 81%), identification of pressure injury risk score/category (from 19 to 88%), employment of nutritional assessment tools (from 8 to 93%), and provision of information regarding oral nutritional supplements (from 23 to 84%). Furthermore, patients learning the pressure injury care protocols (from 48 to 93%), the receipt of additional skin protection measures, and repositioning of vulnerable areas to relieve pressure increased to 100 and 93%, respectively. After project implementation, the monthly pressure injury incidence decreased markedly from 0.075 to 0.021%. Conclusion: The success factors of this project are attributable to leadership, open communication, multiple learning-by-doing strategies, regular audits, and the promotion of patient and family engagement.